Measuring velocities of a surge type glacier with SAR interferometry using ALOS-2 data - Karlsen, Truls (UiT The Arctic University of Norway, 2021)
In recent years, in-situ measurements on Kongsvegen, a surge-type glacier located in the Kongsfjorden area, have showed an acceleration in the flow speeds of the glacier. This could indicate the onset of a surging event, which presents the opportunity to study the dynamics of a glacier surge using remote sensing techniques with in-situ data for reference. Synthetic aperture radar (SAR) is well suited for this, as it does not rely on the sun for illumination and is not obstructed by clouds. In addition, SAR can be used to measure displacement with high accuracy and resolution through the use of interferometric SAR (InSAR). This study investigates the acceleration of Kongsvegen using InSAR, MAI and offset tracking. Velocity measurements from the combination DInSAR - MAI are then compared to in-situ data as well as the offset tracking measurements. For image pairs where InSAR measurements are not possible due to phase decorrelation, offset tracking is attempted as a back-up. Data from 2015, 2018 and 2019 was available, and the evolution of flow speeds over time could therefore be evaluated. The image pairs from 2018-2019 were acquired with 14 days separation in time, while the 2015 image pairs were acquired with 28 and 42 days separation. Due to the longer separation in time, the 2015 image pairs decorrelated in time. In addition, a pair acquired in the summer of 2018 decorrelated as a result of surface melting on the glaciers. Therefore only 3 of the total 8 pairs available were suited for interferometric analysis. For the image pairs from 2018-2019, the InSAR measurements were in good agreement with the in-situ data, as they also indicated an acceleration of the flow speeds on Kongsvegen. The offset tracking results on these pairs overestimated the velocity magnitudes, but also showed an increase in time. Similar to the InSAR estimates, the offset tracking failed to produce reasonable results on the 2015 image pairs, likely because of the large temporal baseline and lack of surface features on Kongsvegen. ...